Possibilities of palliative chemotherapy in patients with locally advanced and metastatic pancreatic cancer - L. I. Moskvicheva; L. V. Bolotina (Исследования и практика в медицине)
Currently, pancreatic cancer remains one of the most unfavorable tumor pathologies, characterized by pronounced difficulties in diagnostics and treatment, a significant impact on the ability to work and quality of life of patients, and low indicators of patient life expectancy. Features of the development of malignant neoplasms of this localization contribute to limiting the possibility of performing radical surgery, and therefore a special role in the treatment of patients with pancreatic cancer is assigned to chemotherapy. Specific systemic drug therapy for this pathology is the most important and, in the majority of cases, mandatory element of treatment. It can be carried out in a neoadjuvant, adjuvant and independent mode, include mono- or multi- component schemes, and be combined with other types of systemic or local antitumor effects. The choice of chemotherapy regimen depends primarily on the General somatic status of the patient and is determined by the potential toxicity of a particular combination of cytostatics. This review of the literature demonstrates the effectiveness of various chemotherapy regimens in patients with stage III–IV pancreatic cancer in the first and second lines, describes the frequency of adverse reactions to treatment and their nature, and mentions ways to reduce the toxicity of multicomponent drug therapy regimens. This review is based on the analysis of scientific sources of the Internet resource "National Center for Biotechnological Information".